ADPase CD39 Fused to Glycoprotein VI‐Fc Boosts Local Antithrombotic Effects at Vascular Lesions - Heidrun Degen; Oliver Borst; Melanie Ziegler; Ann‐Katrin Mojica Munoz; Janina Jamasbi; Britta Walker; Silvia Göbel; Julia Fassbender; Kristin Adler; Richard Brandl; Götz Münch; Reinhard Lorenz; et al. (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2017)
BackgroundGPVI (Glycoprotein VI) is the essential platelet collagen receptor in atherothrombosis. Dimeric GPVI‐Fc (Revacept) binds to GPVI binding sites on plaque collagen. As expected, it did not increase bleeding in clinical studies. GPVI‐Fc is a potent inhibitor of atherosclerotic plaque‐induced platelet aggregation at high shear flow, but its inhibition at low shear flow is limited. We sought to increase the platelet inhibitory potential by fusing GPVI‐Fc to the ectonucleotidase CD39 (fusion protein GPVI‐CD39), which inhibits local ADP accumulation at vascular plaques, and thus to create a lesion‐directed dual antiplatelet therapy that is expected to lack systemic bleeding risks. Methods and ResultsGPVI‐CD39 effectively stimulated local ADP degradation and, compared with GPVI‐Fc alone, led to significantly increased inhibition of ADP‐, collagen‐, and human plaque–induced platelet aggregation in Multiplate aggregometry and plaque‐induced platelet thrombus formation under arterial flow conditions. GPVI‐CD39 did not increase bleeding time in an in vitro assay simulating primary hemostasis. In a mouse model of ferric chloride–induced arterial thrombosis, GPVI‐CD39 effectively delayed vascular thrombosis but did not increase tail bleeding time in vivo. ConclusionsGPVI‐CD39 is a novel approach to increase local antithrombotic activity at sites of atherosclerotic plaque rupture or injury. It enhances GPVI‐Fc–mediated platelet inhibition and presents a potentially effective and safe molecule for the treatment of acute atherothrombotic events, with a favorable risk–benefit ratio.